2014
DOI: 10.3109/01612840.2014.915899
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Placements in Mental Health: A Literature Review

Abstract: Gaining experience in clinical mental health settings is central to the education of health practitioners. To facilitate the ongoing development of knowledge and practice in this area, we performed a review of the literature on clinical placements in mental health settings. Searches in Academic Search Complete, CINAHL, Medline and PsycINFO databases returned 244 records, of which 36 met the selection criteria for this review. Five additional papers were obtained through scanning the reference lists of those pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 43 publications
5
54
0
Order By: Relevance
“…(2015) assert that clinical placements are an important component of the nursing curriculum and can have an influence on attitude (Chadwick & Porter, 2014;Happell et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(2015) assert that clinical placements are an important component of the nursing curriculum and can have an influence on attitude (Chadwick & Porter, 2014;Happell et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Clinical placements in mental health settings are one such factor known to increase student confidence of working in mental health settings, particularly when the placement is perceived by students as positive (Happell et al . ). Clinical placements have also been found to reduce anxieties and fears of working in mental health settings and improve attitudes towards people living with mental illness (Feeney et al .…”
Section: Discussionmentioning
confidence: 97%
“…Further, Happell et al . 's (,b) review of the literature related to clinical placements in mental health found that mental health clinical placements can improve student confidence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have shown that the exposure gained from curriculum and practicum improves the attitudes of student nurses about mental health nursing [25,26,33]. These studies emphasize the importance of establishing closer working relationships between schools of nursing and clinical settings to ensure that nursing students have opportunities to: (1) be actively involved in patient care, (2) be exposed to a positive clinical environment, and (3) have a more comprehensive understanding about PMHN and patients with mental disorders [34]. Anxiety is a strong factor negatively affecting a student nurse's likelihood of entering PMHN, and a sense of preparedness diminishes this anxiety [35], which can be accomplished through arranging positive clinical placements for the students throughout the educational experience.…”
Section: Page 4 Ofmentioning
confidence: 99%